Endometriosis and Assisted Reproductive Technologies: Maximizing Outcomes - Surrey, Eric S. (Seminars in Reproductive Medicine, 2013)
In vitro fertilization (IVF) represents the most efficient means of overcoming endometriosis-related infertility. Compromised pelvic anatomy and a hostile peritoneal environment are bypassed. Despite the results of early trials, more contemporary outcomes data would suggest that when controlled for age, IVF cycle outcome is not compromised by the presence of endometriosis. One exception to this concept is the finding that patients with ovarian endometriomas demonstrate poorer response to gonadotropin therapy, although it is not clear that this affects the likelihood of implantation. Surgical ablation of superficial endometriosis has no clear impact on IVF pregnancy rates, although a small number of recent trials suggest that pre-cycle resection of deeply infiltrative disease may be beneficial. With the exception of traditional gynecologic indications, there is no evidence to suggest that resection of ovarian endometriomas has any positive impact on cycle outcome. There are, in fact, data demonstrating that resection may exert a deleterious effect on ovarian reserve. A subset of patients will benefit from administration of a prolonged course of a gonadotropin-releasing hormone agonist prior to an IVF cycle. However, the characteristics of that subset have not been identified. It would be logical to consider this approach in women with more advanced disease, severe symptoms, and a history of implantation failure. Data on the impact of other pre-cycle medical interventions such as aromatase inhibitors, danazol, or oral contraceptives are more limited. There is also no evidence to suggest that the ovarian stimulation associated with IVF induces progression of endometriosis.
Keywords: endometriosis; in vitro fertilization; GnRH agonist; endometrioma; integrin